Effect of manganese on grain boundary segregation of sulfur in iron - Gesari, Susana Beatriz (2007)
The ASED-MO theory was used to study the electronic effects of S and the S-Mn couple upon the chemical embrittlement of Fe grain boundaries. The results obtained for S alone in a model of grain boundary (GB) are consistent with its observed behavior as a chemical embrittling agent. It was found that the total energy of the cluster decreases when the S atom is located at the GB. When S segregate at the Fe GB containing Mn, the embrittlement process was modified. The crystal orbital overlap population (COOP) curves gives a measure of Fe-Fe bond weakening due to the segregated atoms at the GB. Our calculations show that Mn behaves as a weak embrittler on the Fe GB. The Fe-Mn bonds were strengthened, while Fe-Fe bonds of the capped trigonal prism of the GB (CTP) were weakened. On the other hand, when S segregate at the Mn/Fe cluster, some metallic bonds were resistant to chemical embrittlement. © 2007 Elsevier B.V. All rights reserved.